Penggunaan Metode DNA Jemaat Kevin Graham Ford dalam Analisis Identitas Jemaat GKJ Joglo - Marya Sri Hartati; Lazarus Purwanto (Theologia in Loco, 2020)
This article is about to display the DNA search process of GKJ Joglo by using DNA theory of Kevin Graham Ford congregation. This research is based on the realization that it is important for a church to find its DNA, which is why DNA is moving the whole life of the congregation, even exceeding the formulation of its vision. With qualitative research methods, this paper will start a discussion: the Church’s DNA theory, search process, and research results. Hopefully through the findings of this DNA, the congregation can achieve a complete and profound understanding of itself in the midst of a concrete local context. Then from there he can transform himself to become a community of faith whose presence and service is meaningful and impactful to the wider community.